2011
DOI: 10.1104/pp.111.178897
|View full text |Cite
|
Sign up to set email alerts
|

Plastid-to-Nucleus Retrograde Signals Are Essential for the Expression of Nuclear Starch Biosynthesis Genes during Amyloplast Differentiation in Tobacco BY-2 Cultured Cells    

Abstract: Amyloplasts, a subtype of plastid, are found in nonphotosynthetic tissues responsible for starch synthesis and storage. When tobacco (Nicotiana tabacum) Bright Yellow-2 cells are cultured in the presence of cytokinin instead of auxin, their plastids differentiate from proplastids to amyloplasts. In this program, it is well known that the expression of nucleus-encoded starch biosynthesis genes, such as ADP-Glucose Pyrophosphorylase (AgpS) and Granule-Bound Starch Synthase (GBSS), is specifically induced. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 58 publications
(65 reference statements)
0
40
0
Order By: Relevance
“…In our recent study, 5 we demonstrated transcription of nuclear starch biosynthesis genes was affected specifically by supplementation of inhibitors specific to organelle gene expression (OGE) and tetrapyrrole biosynthesis, which represents the presence of a retrograde signaling pathway(s) similar to that observed between the nucleus and chloroplasts as previously reported. [6][7][8] These two retrograde signals derived from OGE and tetrapyrrole metabolism influenced the efficiency of amyloplast differentiation via positive and negative effects, respectively, on expression of such nuclear genes.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…In our recent study, 5 we demonstrated transcription of nuclear starch biosynthesis genes was affected specifically by supplementation of inhibitors specific to organelle gene expression (OGE) and tetrapyrrole biosynthesis, which represents the presence of a retrograde signaling pathway(s) similar to that observed between the nucleus and chloroplasts as previously reported. [6][7][8] These two retrograde signals derived from OGE and tetrapyrrole metabolism influenced the efficiency of amyloplast differentiation via positive and negative effects, respectively, on expression of such nuclear genes.…”
Section: Introductionmentioning
confidence: 67%
“…By applying a specific differentiation system in tobacco Bright Yellow-2 (BY-2) cultured cells, 3,4 we recently reported that the regulatory system of nuclear gene expressions modulated by a plastid signal was also observed during differentiation of plastids into amyloplasts. 5 While retrograde signaling from plastids was previously speculated to consist of several independent pathways, we found inhibition of OGE and perturbation in the cellular content of one tetrapyrrole intermediate, heme, seemed to interact to regulate amyloplast differentiation. Our results thus highlight the possibility that several sources of retrograde signaling in plastids could be integrated in an intraorganellar manner.…”
mentioning
confidence: 66%
See 3 more Smart Citations